The Influence of Leadership and Organizational Support on Community Commitment and City Image of Bandung - Juanim, Juanim; Ratnamiasih, Ina (International Review of Management and Marketing, 2017)
Brand became something very important for a city. With an interesting brand, it would invite many visitors such as investors, business, as well as tourists. This was related to the expected revenue would increase along with the increase of a city brand. Bandung as a unique city in Indonesia was one of cities that was trying to improve its brand image with various leadership efforts and community commitment. These efforts had resulted in a significant change in visitor interest. This was evident through the results of research on 150 respondents, which showed that leadership and community commitment had a major impact on improving the City Image of Bandung. This research was conducted by distributing questionnaires and interviews on several stakeholders. Several findings had been produced and recommendations had been given for leadership and community commitment to support the improvement of Bandung's city brand image. Keywords: City image, organizational support, leadership, community commitment JEL Classifications: L2, M3